Intangible heritage and education: limits and possibilities of educational actions in the State of Sao Paulo - Goulart, Rafaela Sales [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
This article has as its central theme heritage education and, in this aspect, seeks to reflect on the limits and possibilities of educational actions that involve the idea of safeguarding the intangible cultural heritage of Sao Paulo. To this end, data were collected on University Extension Projects developed in the state of Sao Paulo, between 2009 and 2014; then, other actions were taken from the university field (creation of the Paulista Network of Heritage Education) and from the Brazilian Ministry of Education (manuals prepared by the National Historical and Artistic Heritage Institute and adapted to the More Education Program) in order to take them as possibilities of heritage education, especially in cities not benefited by heritage policies. The limits of educational actions were presented due to the recent history of recognition of immaterial heritage in the Federal Constitution of 1988, the National Curriculum Parameters of 1997 and Decree n degrees. 57.439/2011.
Keywords: Heritage education; Education; Culture; Politics; University